2016
DOI: 10.3846/20294913.2016.1244710
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Standard Value Added Tax on Economic Growth in Cee-5 Countries: Econometric Analysis and Simulations

Abstract: The value added tax (VAT), as an instrument of fiscal policy, might have an important role on economic growth. This study analyzes the impact of standard VAT rate on economic growth in five Central and Eastern European countries (CEE-5) (Bulgaria, Czech Republic, Hungary, Poland and Romania). Different types of panel data models (random effect model, dynamic panel and panel vector-autoregression) over 1995–2015 indicated a positive influence of VAT rate on economic growth. There is a bilateral Granger causalit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
14
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 20 publications
4
14
0
2
Order By: Relevance
“…This conclusion collides with another empirical papers (e.g. Kotlán et al, 2011;Simionescu and Albu, 2016) which showed either insignificant negative impact or slightly positive impact on economic growth. Ebrill et al (2001) state that value added tax creates economic deformations which are smaller compared to other taxes as they reflect lower productivity and savings.…”
Section: Resultssupporting
confidence: 81%
“…This conclusion collides with another empirical papers (e.g. Kotlán et al, 2011;Simionescu and Albu, 2016) which showed either insignificant negative impact or slightly positive impact on economic growth. Ebrill et al (2001) state that value added tax creates economic deformations which are smaller compared to other taxes as they reflect lower productivity and savings.…”
Section: Resultssupporting
confidence: 81%
“…Prichard (2016) highlighted that direct taxes such as personal and corporate income tax are bad for growth compared to indirect taxes. On the other hand, there are many empirical studies that have estimated the relationship between indirect taxes and economic growth (Alm & El-Gannainy, 2012;Li & Lin, 2015;Simionescu et al 2016;Loganathan et al 2017;Kalaš & Milenković, 2017;McNabb, 2018;Dobranschi & Nerudová, 2018). Alm and El-Ganainy (2012) examined relationship between value added tax and consumption in fifteen EU countries for the period 1961-2005.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Results of empirical study confirmed that economic growth in the United States responds negatively to sales tax in the long run, although it produces positive impact in the short run. Empirical analysts Simionescu et al (2016) analyzed the impact of standard value added tax rate on economic growth in Bulgaria, Czech Republic, Hungary, Poland and Romania for the period 1995-2005. Their findings showed bidirectional causality between these variables and negative effect of value added tax rate on economic growth in most observed countries.…”
Section: O I N T E G R a T I O N A N A L Y S I S O F I N D I R E C mentioning
confidence: 99%
“…The outcome of this study aligns with the position of Sok-Gee, Zulkufly, and Mohd Zaini (2017).Adegbite, (2018); Onuora, Okegbe and Ezejiofor (2017); Ibadin and Oladipipo (2016) all agreed with empirical evidence thatValue Added Tax is significant in the Nigerian economy.Results from the studies revealed that Value Added Tax had an overall significant effect on Economic growth and this position aligns with the outcome of this study. Simionescu and Albu (2016) who analysed the importance of Value Added Tax on economic growth in five Central Eastern countries (Bulgaria, Czech Republic, Hungary, Poland & Romania). Dragos (2014) also conducted a study on the Value Added Tax gap in Europe for 2008-2014.…”
Section: Diagnostic Testmentioning
confidence: 99%